La motivación laboral y su relación con la productividad en la industria de hidrocarburos en Colombia (2021)
This descriptive investigative document is intended to show the relationship that work motivation has with the productivity of employees of companies in the hydrocarbon industry in Colombia. Through the documentary review of authors specialized in the subject and the different theories postulated on this subject, it is proposed to develop guidelines for the control of the variables of work motivation, and thus provide tools to the areas of human talent management of organizations, so that they become aware of the need to promote optimal work motivation in human talent, and have the means to develop this initiative. This with the aim that the companies of the union are competitive in a market as changing as that of hydrocarbons.